All systems go again! - Simon Garner; Pederick, Ben.; Boland, Michael, Producer; Video Education America (White Plains, N. Y. Video Education America, 2006)
Bringing VEA's classic, and best selling program All Systems Go into a new era, All Systems Go Again is a fast-moving and lively exploration of the three human energy systems - ATP-PC, Lactic and Aerobic. Concise, up-to-date images and footage will keep students engaged while they investigate the three energy systems of the human body, their intricate links to one another and the way they work in perfect harmony
Writer, Simon Garner; producer Michael Boland.
Voice over, Mark Collard.
Keywords: Bioenergetics; Energy metabolism